POLIMA DALAM PERSPEKTIF HUKUM PEMERINTAHAN DAERAH - Darmawan Wiridin; Hendrik Ruben Gelong; Safrin Salam; Noviyanti Malaha; Ruliah Ruliah (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2022)
The implementation of government leadership based on culture is one solution to overcome the leadership crisis in Indonesia. This type of research uses this type of empirical legal research by pin pointing the research site in Baubau city. The data sources used are primary data and secondary data. Data collection techniques using interviews and literature studies. The results showed that the implementation in the system of government and daily life is an effective and appropriate step, moreover Buton is an area that has a history of sultanate that has long lived with local cultural values, namely Pomaa Masiaka means always living caring for each other and loving each other, Popia-Piara means always living to care for each other. Pomae-Maeka means always glorifying each other, Poangka-Angkataka means mutual respect, and Pobinci-Binciki Kuli pinching each other's skin is an allusion to painful deeds. While Polima is able to be a solution to improve various aspects of life in society because complex cultural values are able to answer the problems that occur now such as corruption, collusion, nepotism, violence, and social problems such as lazy to know the surrounding environment, not mutual respect, and other problems. With the implementation of polima the government and the community will understand each other and understand the role of each will create a safe, peaceful, and prosperous life.